Correlation between APACHE II Score on Mortality Severe Head Injury Patients in the Educational Room of Dr. Mohammad Hoesin General Hospital Palembang in 2019-2020 - Anggi Ciptawan; Trijoso Permono; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2022)
tissue due to trauma. Severe head injuries account for about 10% of the total head injuries. In addition to death caused by severe head injury itself, head injury patients are susceptible to complications that can occur while the patient is hospitalized. The purpose of this study was to determine the correlation between the APACHE II Score on the mortality of severe head injury patients who were treated in the GICU room, Dr. Mohammad Hoesin Palembang. This type of research is a quantitative research using a retrospective analytical study survey design. Between group variables are unpaired because no matching is done. The research sample is 30 respondents. Results of analysis in this study, after statistical testing using the Chi Square test, p value < 0. 002 was obtained which clarified that there was a relationship between APACHE II Score and mortality in respondents with severe head injuries who were treated in the GICU, Dr. Mohammad Hoesin Palembang. Severe head injury in the GICU room, Dr. Mohammad Hoesin Palembang (p=0.002). The higher the patient's APACHE II score, the more likely the patient to leave the GICU dead. From a total of 30 respondents who were treated in the GICU room, the highest APACHE II score was 28 and the lowest was 3 the more likely the patient to leave the GICU dead. From a total of 30 respondents who were treated in the GICU room, the highest APACHE II score was 28 and the lowest was 3 the more likely the patient to leave the GICU dead. From a total of 30 respondents who were treated in the GICU room, the highest APACHE II score was 28 and the lowest was 3.